SOTEOROLOGI DAN EKARISTI: PEMAHAMAN SAKRAMEN PERJAMUAN KUDUS MENURUT JOHN CALVIN DAN IMPLIKASINYA BAGI KEHIDUPAN JEMAAT - Tinggi Tandi Payuk; Dwi Jumartini Sombolola’, Adil Masokan Paembonan, Johan Tandibua’, Dinda Putri Aprilianty S. (ADISAM PUBLISHER, 2023)
The Sacrament of Holy Communion is a crucial aspect of Christian theology with diverse understandings and interpretations. One significant perspective is that of John Calvin, a Protestant Reformation theologian. This article elucidates Calvin's understanding of the Sacrament of Holy Communion and its implications for the life of the congregation. According to Calvin, the Sacrament of Holy Communion is a sign of God's grace that provides spiritual nourishment to the congregation. Calvin perceives Holy Communion as a symbol conveying spiritual reality. He rejects the doctrine of Transubstantiation, which he views as erroneous, and instead presents the perspective of Consubstantiation, where Christ is spiritually present in the elements of Holy Communion. For Calvin, the physical elements (bread and wine) remain in their physical form, but Christ is spiritually present to bless and strengthen the faith of the congregation. The implications of Calvin's understanding of the Sacrament of Holy Communion for the life of the congregation are manifold. Firstly, Calvin emphasizes the importance of active participation by the congregation in Holy Communion. This prompts the idea that the congregation should celebrate Holy Communion regularly as a sign of their fidelity to Christ. This activity strengthens the communion between the congregation and Christ. Secondly, Calvin teaches that Holy Communion serves as a reminder of Christ's death and the forgiveness of our sins through His sacrifice. It reminds the congregation of the importance of repentance and righteous living in accordance with Christ's teachings. Thirdly, Calvin also connects the Sacrament of Holy Communion with an understanding of the body of Christ, which is the church. This encourages the congregation to be attentive to the welfare of others and participate in the service and fellowship of the church. Thus, John Calvin's understanding of the Sacrament of Holy Communion has profound implications for the life of the congregation. It encourages activity, awareness of God's grace, repentance, and fidelity to the teachings of Christ. In Calvin's view, the Sacrament of Holy Communion is a powerful instrument for strengthening the faith and commitment of the congregation to Christ and the church.